ORGANIZATIONAL CULTURE TRANSFORMATION AND ITS IMPACT ON EMPLOYEE PERFORMANCE IN THE READY-FOOD SECTOR - Fari Aus; Nada Kusuma; Muh. Husriadi (CV. Adiba Aisha Amira, 2025)
The fast food industry has experienced rapid growth over the decades, making it one of the most dynamic sectors in global and local markets. This research explores how to change organizational culture and influence employee motivation and organizational performance in this sector. This research aims to encourage interactions between organizations and performance. Using qualitative methods including in-depth interviews and participant observation, it was found that the application of values such as cooperation and honesty builds a cooperative work environment, increasing employee engagement and productivity. Leadership commitment has been proven to overcome challenges and ensure the success of cultural change. Practical recommendations include a focus on strengthening cultural values within oneself and open communication between teams . Future research could expand the scope of the sample and include other industries to increase the generalizability of the findings and explore broader implications for customer satisfaction and long-term network operations.